2021
DOI: 10.48550/arxiv.2107.14346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Networks for Parameter Estimation in Intractable Models

Abstract: We propose to use deep learning to estimate parameters in statistical models when standard likelihood estimation methods are computationally infeasible. We show how to estimate parameters from max-stable processes, where inference is exceptionally challenging even with small datasets but simulation is straightforward. We use data from model simulations as input and train deep neural networks to learn statistical parameters. Our neural-network-based method provides a competitive alternative to current approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Gerber & Nychka (2021) showed that their CNN estimator was comparable to the maximum likelihood estimator in terms of bias and variance and, like Zammit-Mangion & Wikle (2020), reported a hundred-fold speed up in estimation. Lenzi et al (2021) considered a similar CNN framework for estimating parameters in models of spatial extremes. This approach to parameter estimation is still in its infancy in spatial statistics, but has seen wide use in a variety of related areas that require parameter estimation.…”
Section: Deep Learning For Parameter Estimation In Spatial and Spatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gerber & Nychka (2021) showed that their CNN estimator was comparable to the maximum likelihood estimator in terms of bias and variance and, like Zammit-Mangion & Wikle (2020), reported a hundred-fold speed up in estimation. Lenzi et al (2021) considered a similar CNN framework for estimating parameters in models of spatial extremes. This approach to parameter estimation is still in its infancy in spatial statistics, but has seen wide use in a variety of related areas that require parameter estimation.…”
Section: Deep Learning For Parameter Estimation In Spatial and Spatio...mentioning
confidence: 99%
“…• Lenzi et al (2021) use deep learning to estimate parameters with statistical spatial models of extremes, whose likelihood is intractable or difficult to evaluate. They apply their methods for efficiently estimating parameters in a Brown-Resnick process fitted to surface temperature data.…”
Section: Introductionmentioning
confidence: 99%
“…[3] provided universal approximation results for functions on finite dimensional topological spaces; that is, if F is dense in C(R n ; R m ), then {f • ϕ : f ∈ F } is dense in C(X ; R m ) when ϕ : X → R n is continuous and injective. [4] used distributional neural networks to estimate parameters for max-stable processes. [5] does density estimation using neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Huser et al (2022) have also applied the Vecchia approximation that requires only moderate-dimensional (say 10 or 15) joint distribution functions, which are available for some MSPs. Deep learning has been used to estimate parameters in spatial models (Gerber and Nychka, 2021;Lenzi et al, 2021) by simulating datasets with different parameter values and using deep learning to identify features of the simulated data that are indicative of particular parameter values. However, it is difficult to extend them to problems with many parameters such as the spatio-temporally varying coefficients (STVC) case that are crucial to our application.…”
Section: Introductionmentioning
confidence: 99%